Advances in Soil Pollution and Geotechnical Environment - Bai, Bing (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This is a reprint of articles from the Special Issue published online in the open access journal Applied Sciences (ISSN 2076-3417). This book addresses the most recent developments in soil pollution and restoration, contaminant hydrology, and ground disturbance to stimulate fruitful technical and scientific interactions between professionals.